Cost-benefit analysis and equitable cost allocation for a residential rainwater harvesting system in the city of Austin, Texas. Issue 5 (2nd September 2016) - Kim, Hyun Woo; Li, Ming-Han; Kim, Hyun; Lee, Hye Kyung
Abstract: This study addresses the applicability and financial feasibility of residential rainwater harvesting systems in the city of Austin, Texas. A cost-benefit analysis is used to estimate the financial return for individual households with rainwater harvesting systems. In addition, a subsidy value that could be provided by the delay of a wastewater treatment plant expansion project is investigated. The findings suggest that a residential rainwater harvesting system would not be feasible without a sufficient subsidy. The estimated subsidy is also not enough to make the cost of the harvesting system effective; however, its multi-purpose benefits are not quantified.